Capabilities for service innovation: A qualitative case study in the consulting industry - Plattfaut, Ralf; Niehaves, Björn; Becker, Jörg (16th Pacific Asia Conference on Information Systems, 2012)
In today’s dynamic market environments, service organizations face the need to improve existing and create new services. While practice and research acknowledge the importance of this phenomenon, it is yet understudied with regard to understanding relevant resources for service innovation. Based on the resource-based view and dynamic capability theory, we develop a theoretical understanding of service innovation. In order to identify relevant resources, here: capabilities and assets, we conduct a qualitative case study at IT-CONSULT, a Germany-based IT consultancy. Results suggest that the current understanding of dynamic capabilities is unable to explain the occurrences at IT-CONSULT. Thus, we discuss the extension of the dynamic capability framework with a new class of capabilities – systemic capabilities – that function to mobilize operational capabilities and assets. Implications of this research for both theory and practice are discussed.